2002
DOI: 10.1006/viro.2001.1344
|View full text |Cite
|
Sign up to set email alerts
|

The Complete Genome Sequence of Perina nuda Picorna-like Virus, An Insect-Infecting RNA Virus with a Genome Organization Similar to That of the Mammalian Picornaviruses

Abstract: Perina nuda picorna-like virus (PnPV) is an insect-infecting RNA virus with morphological and physicochemical characters similar to the Picornaviridae. In this article, we determine the complete genome sequence and analyze the gene organization of PnPV. The genome of PnPV consists of 9476 nucleotides (nts) excluding the poly(A) tail and contains a single large open reading frame (ORF) of 8958 nts (2986 codons) flanked by 473 and 45 nt noncoding regions on the 5' and 3' ends, respectively. Northern blotting did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
46
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 50 publications
3
46
0
Order By: Relevance
“…)] and resembles the hairpin structures found close to the 59 termini of the genomic RNAs of Perina nuda virus (PnV) and Ectropis obliqua picorna-like virus (EoPV) (Ongus et al, 2006;Wang et al, 2004;Wu et al, 2002 )], which do not have much in common with those identified in other iflaviruses (Ongus et al, 2006). High diversity of the 59-NTR secondary structure elements has been reported, for example, in the family Picornaviridae (Witwer et al, 2001).…”
mentioning
confidence: 96%
“…)] and resembles the hairpin structures found close to the 59 termini of the genomic RNAs of Perina nuda virus (PnV) and Ectropis obliqua picorna-like virus (EoPV) (Ongus et al, 2006;Wang et al, 2004;Wu et al, 2002 )], which do not have much in common with those identified in other iflaviruses (Ongus et al, 2006). High diversity of the 59-NTR secondary structure elements has been reported, for example, in the family Picornaviridae (Witwer et al, 2001).…”
mentioning
confidence: 96%
“…The first PnPV 2A-encoding RNA sequence, codons 556-573, with the potential to code for QGWVPDLTVDGDVESNPG is at the 39 end of the cp1 gene and the first codon, 574, of the adjacent cp2 gene specifies proline. This proline was confirmed by N-terminal sequence analysis (Wu et al 2002). The second PnPV 2A-encoding RNA sequence, codons 1173-1190, with the potential to code for GGGQKDLTQDGDIESNPG, is in the vicinity of the predicted 39 end of the cp4 gene and the 39 adjacent codon, 1191, is a proline codon (Wu et al 2002).…”
Section: Introductionmentioning
confidence: 75%
“…The single-stranded RNA Perina nuda picorna-like virus, PnPV, which infects a moth, has these features and also has an additional 2A-encoding sequence where only the upstreamencoded product is present in the virion ( Fig. 1; Wu et al 2002). This virus can be readily propagated in a homologous insect cell line (Wu et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations